Phytochemical Properties, Antioxidant, and Cytotoxicity Activity of Knobweed (Hyptis capitata) from South Sulawesi, Indonesia - To'bungan, Nelsiani; Widhiastuti, Stefani Santi; Hida, Fitriana Nur Laissya; Mahardhika, I Wayan Swarautama (Universitas Gadjah Mada, 2024)
Hyptis capitata Jacq. known as Sumambu plants in Sulawesi, has phytopharmaceutical importance. H. capitata extracts were evaluated for their phytochemical properties, antioxidant activity, and cytotoxicity. Using the maceration yielded five types of extracts: root chloroform (RC), root methanol (RM), leaf chloroform (LC), leaf methanol (LM), and leaf ethanol (LE). Phytochemical properties were identified by qualifying procedure and digital image analysis for quantifying Red-Green-Blue (RGB) percentage and hex colour code. 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay was used to determine the half-maximal inhibitory concentration (IC50). Cytotoxicity screening of each extract was performed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay against HeLa and 4T1 cells. Gas Chromatography-Mass Spectrometry (GC-MS) assay was used to identify the phytochemical compounds of the extracts with the most promising potential. Alkaloids were the major constituents of the phytochemicals of RC, RM, LE, LC, and LM. RM and LM have potency and weak free radical scavenging activities, with IC50 value 31.08 and 58.03 µg/mL, respectively. The IC50 of RC and RM against HeLa cells were 84.21 ± 0.63 and 172.10 ± 02.90 µg/mL, respectively. Meanwhile, the cytotoxicity of RC and RM against 4T1 cells were 86.42 ± 0.80 and 182.82 ± 7.00 µg/mL, respectively. It means RC and RM exhibit a moderate level of cytotoxicity in both HeLa and 4T1 cells. LM shows moderate cytotoxicity, but it is limited to 4T1 cells with an IC50 value of 181.86 ± 12.68 µg/mL. The cytotoxicity level of extracts was lower than doxorubicin. Campesterol, ferruginol, stigmasterol, cis-13-octadecenoic acid methyl esters, and methyl palmitate were predicted to play a role in the antioxidant activity and cytotoxicity of RC, RM, and LM. RC, RM, and LM possess the potential for development as anticancer agents. Moreover, RM shows promise as an antioxidant due to its notable radical scavenging activity. Further research is required to explore the cytotoxic effects of RC, RM, and LM on normal cells and to assess their toxicity in experimental animals.